ANALISIS KESALAHAN EJAAN PADA SALAH SATU JUDUL BERITA “ISU TKA DIGORENG MENJELANG PILPRES” PADA SURAT KABAR TRIBUN JABAR EDISI 25 APRIL 2018 - Kurniasari, Nia; Andrianti, Vika; Isnaini, Heri (IKIP Siliwangi, 2018)
This research discusses about various spelling errors that aimed to analyze (1) misuse of acronym or abbreviation (2) misapplication of capitalization (3) mistyping words in one of the news titles “ Isu TKA Menjelang Pilpres” on Tribun newspaper 2018 edition. To focus the research then the researcher in the newspaper. This research uses descriptive qualitative method by using data collecting technique that is looking for newspaper and read it. While the research instrument is the researcher himself and the description of errors and improvement. Data analyst techniques used are reading, marking errors, identifying, analyzing and concluding. The result of this study indicated that the erroneous use of Indonesian spelling on one of the headline in the newspaper Tribun Jabar edition 25 April 2018 as many as 6 (six) spelling mistakes consisting of : (1) errors in the use of acronyms by 1 (one) errors, (2) misapplication of capital letters of 2 (two) errors, (3) mistyping mistakes 1 (one) error, (4) the connect error is 1 (one) error, (5) mistakes writing people names as many as 1 (one) error.